INTERNET AS CONNECTING GAP IN GUIDING INFORMATION (Case Study: Kampung Media in KSB For Access to Information on Villagers) - - Yusmawati (Jurnal Komunikasi, 2017)
The internet is a new communication medium that is already familiar to the community. Any form of communication activity can be done through the internet. Internet users have penetrated various circles and in various places, including in remote areas of Indonesia. Kabupaten Sumbawa Barat is one of the regencies located in the province of Nusa Tenggara Barat. In terms of geography, the location of the district is fairly far from other major cities, including the central government of Jakarta. However, this great distance does not make the people there blind of technology and information. This study aims to find out how the internet as a gap leverage in obtaining information. The research method used is case study with qualitative approach. Data obtained through interviews, literature study, and documentation. The results showed that internet-based Kampung Media help the community in Nusa Tenggara Barat, especially in Kabupaten Sumbawa Barat to obtain ease in obtaining information via the internet. Society is no longer isolated in obtaining information, even can compete with other regions in Indonesia. In addition to getting information, Kampung Media community also provides an opportunity for the community there to provide information to other communities in various regions. Become a useful society. Keyword: Internet, Gap, Kampung Media